TGFβ Causes Postoperative Natural Killer Cell Paralysis Through mTOR Inhibition - Market, Marisa Rae (Université d'Ottawa / University of Ottawa, 2020)
Background: Life-prolonging tumour removal surgery is associated with increased metastasis and disease recurrence. Natural Killer (NK) cells are critical for the anti-tumour immune response. Postoperatively, NK cell cytotoxicity and interferon-gamma (IFNγ) production are profoundly suppressed and this dysfunction has been linked to increased metastases/poor patient outcomes. NK cell activity depends on the integration of signals through receptors and can be modulated by soluble factors, including transforming growth factor- beta (TGFβ). The postoperative period is characterized by the expansion of myeloid-derived suppressor cells (sxMDSCs), which inhibit NK cell effector functions. I hypothesize that impaired NK cell IFNγ production is due to altered signaling pathways caused by sxMDSC-derived TGFβ. Methods: Postoperative changes in NK cell receptor expression, receptor-dependent phosphorylation of downstream targets, and rIL-2/12-stimulated IFNγ production were assessed using newly developed whole blood assays utilizing peripheral blood samples from cancer surgery patients. Isolated healthy NK cells were incubated in the presence of healthy/baseline/postoperative day (POD) 1 plasma or isolated sxMDSCs and NK cell phenotype and function were assessed. NK cells were also cultured with plasma in the presence/absence of a TGFβ blocking monoclonal antibody (mAb) or a TGFβ RI small molecule inhibitor (smi). Single-cell RNA-sequencing was performed on six colorectal cancer surgery patients at baseline and on POD1. S6 phosphorylation was used as a proxy for mammalian target of rapamycin complex (mTORC) 1 activity to investigate the mechanism of TGFβ-mediated NK cell dysfunction. Results: Intracellular NK cell IFNγ, activating receptors CD132 (IL-2R), CD212 (IL-12R), NKG2D, and DNAM-1, and the phosphorylation of downstream targets STAT5, STAT4, p38 MAPK, and S6 were significantly reduced on POD1. TGFβ was increased in patient plasma on POD1. The dysfunctional phenotype could be phenocopied in healthy NK cells through the addition of rTGFβ1 or by incubation with POD1 plasma. This dysfunctional phenotype could be prevented with the addition of an anti-TGFβ mAb or a TGFβ RI smi in culture. RNA-sequencing revealed a reduction in transcripts associated with mTOR effector functions, suggesting an impairment in mTOR. S6 phosphorylation was maintained with the addition of TGFβ-specific therapies. The hyporesponsive NK cell phenotype was reproduced upon culture of healthy NK cells with sxMDSCs and sxMDSCs were shown to produce soluble TGFβ in culture. Conclusion: Surgically stressed NK cells display a dysfunctional phenotype, which could be prevented in vitro through the addition of TGFβ-specific blocking therapies. sxMDSCs produced TGFβ and co- incubation induced dysfunction in healthy NK cells. The recovery of impaired S6 phosphorylation with TGFβ-specific therapies suggests that TGFβ is inducing NK cell dysfunction via inhibition of mTORC1 activity. The perioperative period of immunosuppression presents a window of opportunity for novel therapeutics to prevent metastases and cancer recurrence among cancer surgery patients.
Keywords: Natural Killer cells; Interferon gamma; Transforming growth factor beta; Surgery